Analysis of the computerized activities included in Palestinian Mathematics textbooks - Jebreel Karama, Muneer (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
Purpose– The study aimed to analyze the standards of computerized activities included in mathematics textbooks based on international standards and indicators. Design/methodology/approach–The researcher developed a tool (content analysis) to analyze these activities and verified its validity and reliability. This tool was then applied to a sample of mathematics textbooks. Findings –The results revealed a significant gap between the expected standards and indicators and the actual standards and indicators found in the mathematics textbooks. Originality/value – It is crucial to consider fundamental international standards in utilizing computer software in mathematics textbooks, including the design of mathematical tasks, posing mathematical questions, facilitating and simplifying mathematical discussions, and assessing student learning. Based on these findings, the researcher recommended a reassessment of the development of computerized activities in mathematics textbooks.